The University Life Café: Promoting Students’ Emotional Health - Hai-Jew, Shalin; Anders, Brent A. (My University, 2010)
With the popularization of socio-technical online spaces (high-tech spaces through which people interact, collaborate, and co-create), Web 2.0 ("Social Web") information technologies offer a new tool for the creation of protective factors against suicide, including a virtual student community. Raising awareness of suicide and de-stigmatizing that awareness are critical elements in building protective factors around students. It was in this spirit that Kansas State University began work on a website that would eventually become the University Life Café under the auspices of a federal grant from the Substance Abuse and Mental Health Services Administration (SAMHSA). The University Life Café aligns with university endeavors supporting student development of coping skills.
Keywords: University students; Emotional health; Student engagement; Stress management; Websites; Relationships; Life skills; Video; Suicide